DISTANCE EDUCATION IN UNDERGRADUATE PHYSIOTHERAPY PROGRAMS: A SYSTEMATIC REVIEW. - YAŞA, Mustafa Ertuğrul; MADEN, Tuba; ÖZKUTLU, Özge; ÜN YILDIRIM, Necmiye; BAYRAMLAR, Kezban; YAKUT, Yavuz (Turkish Journal of Physiotherapy Rehabilitation, 2024)
Purpose: The use of distance education (DE) models and tools has become increasingly popular in health profession education, including physiotherapy (PT). However, there are few reviews focusing on DE in PT education, which could enable researchers to access comprehensive information, and reviews on various health profession groups often do not include physiotherapy studies. The aim of this study was to synthesize existing evidence and determine the effectiveness of DE systems in PT education. Methods: This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. PubMed, Scopus, EBSCO, Web of Science, and ERIC were searched from inception to July 2020. The initial search resulted in 689 studies. The risk of bias was assessed using the Cochrane risk of bias tool. Results: In this systematic review, 25 studies which included 2129 physiotherapy undergraduate students (11 DE models / 14 e-systems) were found suitable for review. Generally, outcome measures were students' knowledge, satisfaction, and skill. In 16 of the studies, the level of knowledge was investigated, and it was found that the knowledge increased. In 38% of these studies, the increase in the knowledge level of traditional education and DE was similar. It was found that 79% of the studies demonstrated an increase in satisfaction, 14% demonstrated a decrease in satisfaction, and satisfaction with traditional education and DE was similar in 7%. Skill was investigated in 12% of the studies, and all the studies showed the positive effects of DE. Conclusion: DE can promote learning in undergraduate PT education, even though its effectiveness in some areas, such as practical skill acquisition or cost, is controversial. Further high-quality studies with long follow-up periods are needed to investigate the various aspects of the PT curriculum, including both theoretical and practical courses.